Recurrent Metastasis of Epithelial Ovarian Cancer in Cervical, Submandibular and Suboccipital Lymph Nodes (Journal of Medicine, 2009)
Ovarian carcinoma is the second most common gynecologic cancer and the leading cause of death from gynecologic malignancy. The management of recurrent ovarian cancer has been individualized. Reports of recurrence in supradiaphragmatic lymph nodes are rare. We describe the finding of metastatic tumor involving cervical, submandibular and suboccipital lymph nodes in a 77-year-old patient with ovarian carcinoma. Keywords: scalene lymph node, ovarian cancer, lymphadenopathy, recurrence   doi: 10.3329/jom.v10i2.2830   J MEDICINE 2009; 10 : 128-131